2022
DOI: 10.1021/acs.langmuir.2c02250
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Self-Adhesive Lubricated Coating for the Surface Functionalization of Implanted Biomedical Devices

Abstract: The lubrication property of implanted biomedical devices is of great significance as it affects the clinical performance owing to direct contact with soft tissues. In the present study, a bioinspired copolymer with dual functions of both self-adhesion and lubrication was synthesized with N-(3-aminopropyl) methacrylamide hydrochloride, gallic acid, and 3-[dimethyl-[2-(2-methylprop-2-enoyloxy) ethyl] azaniumyl] propane-1-sulfonate by free radical polymerization and a carbodiimide coupling reaction. The copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In a previous study, we proposed the synthesis of a copolymer, namely, PASGA by the carbodiimide coupling reaction of gallic acid and a polymer (PAPSBMA), which was synthesized by free radical polymerization of N -(3-aminopropyl) methacrylamide hydrochloride and sulfobetaine methacrylate . This PASGA copolymer, equipped with self-adhesive and zwitterionic groups, demonstrated superior lubrication and stability both macro- and microscopically.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we proposed the synthesis of a copolymer, namely, PASGA by the carbodiimide coupling reaction of gallic acid and a polymer (PAPSBMA), which was synthesized by free radical polymerization of N -(3-aminopropyl) methacrylamide hydrochloride and sulfobetaine methacrylate . This PASGA copolymer, equipped with self-adhesive and zwitterionic groups, demonstrated superior lubrication and stability both macro- and microscopically.…”
Section: Introductionmentioning
confidence: 99%
“…Although antibiotics and anticoagulants are effective against infection and thrombosis, there may be potential side effects such as fever, antibiotic resistance, and bleeding. In contrast to systemic drug delivery that primarily provides a short-term effect, the surface modification strategy can provide a long-lasting effect and endow the surface with specific functions without altering the main properties of biomaterial, thus offering a promising option for addressing the clinical complications of biomedical devices. The zwitterionic polymer coatings, as one of the representative surface modification methods, have been widely investigated due to their excellent hemocompatibility and antifouling performances. Poly­(2-methacryloyloxyethyl phosphorylcholine) (PMPC), as a typical zwitterionic polymer with repeated units that contain both positively and negatively charged groups, is able to strongly retain water and form a dense and stable hydration layer . Previous studies have demonstrated that the hydration layer formed by zwitterionic polymers can effectively prevent non-specific adhesion of proteins and bacteria, thereby avoiding the subsequent formation of thrombosis and biofilm .…”
Section: Introductionmentioning
confidence: 99%
“…As a silicone polymer with stable physical-chemical properties and good biocompatibility, polydimethylsiloxane (PDMS) has been widely applied in many biomedical applications (catheters, stents, cosmetic implants, etc. ). However, the nonpolar silicon–oxygen chain and special self-helical molecular structure of silicone rubber materials make their surfaces have extremely low surface energy and thus show strong hydrophobicity. , Hydrophobic materials exhibit poor antiwear effects in water environments. , This may lead to greater frictional resistance when silicone rubber medical devices (such as interventional catheters) are squeezed and sheared in the soft tissues of the human body. This results in adverse symptoms in the medical process (such as tissue damage and ulcers). In addition, the surface of hydrophobic medical catheters easily adsorbs small biomolecules (such as proteins and bacteria), and the surface of long-term used catheters is prone to form biofilms, which increases the risk of infection. To alleviate patient discomfort caused by the use of interventional medical devices, glycerin and other lubricants are usually used in clinical practice to reduce the frictional resistance between these devices and soft tissues.…”
Section: Introductionmentioning
confidence: 99%